Star Allele-Based Haplotyping versus Gene-Wise Variant Burden Scoring for Predicting 6-Mercaptopurine Intolerance in Pediatric Acute Lymphoblastic Leukemia Patients - Park, Yoomi; Kim, Hyery; Choi, Jung Yoon; Yun, Sunmin; Min, Byung-Joo; Seo, Myung-Eui; Im, Ho Joon; Kang, Hyoung Jin; Kim, Ju Han (Frontiers in Pharmacology, 2019)
NUDT15 and TPMT are strong genetic determinants of thiopurine toxicity in pediatric acute lymphoblastic leukemia (ALL) patients. Since patients with NUDT15 or TPMT deficiency suffer severe adverse drug reactions, star (*) allele-based haplotypes have been used to predict an optimal 6-mercaptopurine (6-MP) dosing. However, star allele haplotyping suffers from insufficient, inconsistent and even conflicting designations with uncertain and/or unknown functional alleles. Gene-wise variant burden (GVB) scoring enables us to utilize next generation sequencing data to predict 6-MP intolerance in children with ALL. Whole exome sequencing was performed for 244 pediatric ALL patients under 6-MP treatments. We assigned star alleles with PharmGKB haplotype set translational table. GVB for NUDT15 and TPMT was computed by aggregating in silico deleteriousness scores of multiple coding variants for each gene. Poor last-cycle dose intensity percent (DIP < 25%) was considered as 6-MP intolerance, resulting therapeutic failure of ALL. DIPs showed significant differences (p<0.05) among NUDT15 poor (PM, n=1), intermediate (IM, n=48) and normal (NM, n=195) metabolizers. TPMT exhibited no PM and only seven IMs. GVB showed significant differences among the different haplotype groups of both NUDT15 and TPMT (p<0.05). Kruskal-Wallis test for DIP values showed statistical significances for the seven different GVB score bins of NUDT15. GVB NUDT15 outperformed the star allele-based haplotypes in predicting patients with reduced last-cycle DIPs at all DIP threshold levels (i.e., 5, 10, 15, 25%). In NUDT15-and-TPMT combined interaction analyses, GVB NUDT15,TPMT outperformed star alleles (AUROC=0.677 vs. 0.645) in specificity (0.813 vs. 0.796), sensitivity (0.526 vs, 0.474), and positive (0.192 vs. 0.164) and negative (0.953 vs. 0.947) predictive values. Overall, GVB correctly classified five more patients (i.e., one into below and four into above 25% DIP groups) than star allele haplotypes. GVB analysis demonstrated that 6-MP intolerance in pediatric ALL can be reliably predicted by aggregating NGS-based common, rare, and novel variants together, without hampering the predictive power of the conventional haplotype analysis.